(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Myositis ossificans is a reactive lesion that occurs in skeletal muscle. Individuals presenting with myositis ossificans usually with a history of trauma to the involved muscle. We are presenting a case of 18 years old female had a history of trauma 2 years back. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 44-46